Inflammatory pseudotumor simulating malignancy: a rare complication after total hip arthroplasty: Malignomu podoben vnetni pseudotumor: redek zaplet popolne artroplastike kolka - Repše-Fokter, Alenka; Fokter, Samo Karl (Acta Medico-Biotechnica, 2021)
Purpose: Particulate debris created by accelerated polyethylene wear in totally replaced hips causes adverse local reactions. We report an extreme form of such a reaction in a patient who developed progressive thigh pain, weakness and numbness after total arthroplasty of his left hip.Methods: An abdominopelvic computed tomogram showed a large intrapelvic cystic mass interpreted as a malignant tumor. Dark grayish-green fluid was aspirated from the cyst and cytopathologic examination showed necrotic debris without malignant cells. Biopsy revealed necrosis and abundant foreign body granulation tissue with polarizable debris.Results: During surgical removal of the cyst a defect of the inner acetabular wall was noted. After successful revision arthroplasty with allograft bone the clinical symptoms improved.Conclusion: A foreign-body reaction to wear debris may produce an intrapelvic mass and corresponding symptoms. Cytologic and histologic examination of the mass or fluid may aid in interpreting the clinical picture and imaging studies.
Keywords: total hip arthroplasty; intrapelvic mass; foreign body reaction; wear debris